Association Study of Vitamin D Receptor (VDR) - Related Genetic Polymorphisms and their Haplotypes with Chronic Periodontitis in Colombian Population. (2017)
ABSTRACT: Introduction: There is strong evidence that both genetic and environmental factors may affect the periodontal clinical status. However, epidemiological evidence on the association between Vitamin D Receptor (VDR) polymorphisms and Chronic Periodontitis (CP) has been inconsistent. AIM: The focus of this study was to identify if a possible association between VDR Single-Nucleotide Polymorphisms (SNPs) may be implicated in the aetiopathogenesis of CP in Colombian population. Materials and Methods: One hundred and ten CP patients and 50 Healthy Controls (HC) were recruited. Periodontal status was assessed based on probing depth, clinical attachment level, extent, and severity of periodontal breakdown. The polymerase chain reaction-restriction fragment length polymorphism method was used to identify the VDR rs7975232, rs1544410, rs2228570, and rs731236 SNPs from saliva samples. Odds Ratios (ORs) along with their 95% Confidence Intervals (CIs) were computed to compare the distribution of genotypes/alleles between HC and CP patients, alongside with analysis of Linkage Disequilibrium (LD) and haplotype associations between SNPs. Also, an analysis of the interaction between genetic findings and those significant demographic factors was performed for all SNPs. Results: There was no association neither between the different genotypes/allele frequencies nor haplotypes and CP. Similarly, no significant differences in extent or severity amongst genotype/allele groups were observed. Even so, interaction analysis revealed significant synergistic interactions between each SNP and age associated with the disease status. Conclusion: Although these results do not support that VDR SNPs could be identified as independent risk predictor variables for CP in the Colombian population, synergistic biological interactive effects of all these SNPs related to age might play a significant role in the pathogenic pathways of CP.